Analisis Sifat Mekanik dan Struktur Mikro pada Sambungan Las Aluminium dengan Variasi Filler Menggunakan Metode Friction Stir Welding (FSW) - Kristianto, Eko; , Agus Dwi Anggono, ST, M.Eng, Ph.D (2017)
The research topic of aluminium alloys joinning techniques have been improved to optimize the process and to increase the tensile strength. The joinning process of aluminium alloys can be conducted by using Friction Stir Welding (FSW). The research objective was to investigate the mechanics structures of tensile strength of FSW and to see the micro structure of the specimens. The material used in the research was aluminium alloy 6061-T6 series. In this process, it will be used filler mateials of brass and zinc plate. Therefore, the specimens variations were FSW with filler and without filler. According to the tensile test, the FSW welding of aluminium alloy 6061-T6 without filler was delivered the highest tensile strength compared with specimen using filler material. It was delivered 152.2633 MPa of tensile strengt and strain of 3.3733%. From the hardness test, the specimen of FSW without filler was given lower hardness compared with the base metal in the weld nugget. It was 53.1 HV. While the specimen with filler material was delivered hardness higher than without filler. It was 82.8 HV for the brass filler and 122.1 HV for the zinc filler. According to the hardness experiment, it can be seen that the use of filler material during FSW process can increase the HAZ area. The weld nugget of FSW without filler wass seen smoth grain size in photo micro. While the specimen of FSW with filler material was generated bigger grain size which was distributed in aluminium matrix and develop composite structure.